A beginner's guide to mantle of the expert : a transformative approach to education - Taylor, Tim, ....- (Norwich : Singular Publishing, 2016)
Welcome to Mantle of the Expert, a teaching and learning approach that uses drama and inquiry to generate fictional contexts and give children this experience. This book guides the reader through both the broad concepts behind the approach and the detailed steps within it. Drawing on years of experience in the classroom, he gives examples, shares anecdotes, and reassures newcomers to Mantle of the Expert that success is within reach
Keywords: Onderwijs